Competition and Demographics in Large Indian Cities - Amin, Mohammad (Taylor and Francis, 2013)
Recent studies suggest that consumer-household attributes may be as important in determining the level of competition in certain markets as firm characteristics and the number of firms. However, evidence on which consumer-household attributes matter for competition is limited, especially for developing countries. Focusing on India's retail sector, this article contributes to this literature by showing that the number of adult non-workers per household in the city, a proxy for shopping time opportunity cost, has a strong effect on competition between retailers. Policy implications of our findings in light of the ongoing dramatic reductions in non-workers in India are discussed.